World Practice in the Evolution of Public-Private Partnership of Infrastructure Projects - Irina, Calugareanu; Veronica, Bulat (International Journal of Economics, Business and Management Studies, 2022)
The purpose of this article is to analyze historical course, contemporary trends and directions in the worldwide evolutionary development of public-private partnerships, as well as to determine the use of PPP mechanisms as a result of the significant decrease of countries’ budgets and the gap in financial resources that could be used in improvement of their efficiency. The public-private partnership in contemporary conditions becomes a driver of economic development, a basis for modernization, and a factor for increasing the country’s competitiveness, which determines the development of infrastructure, potential in the construction and modernization of a complex of socio-economically significant objects. The concept of public-private partnership (PPP) is widespread worldwide. The study demonstrated that in developed countries the establishment of a public-private partnership system is playing an increasingly important role, and the cooperation between partners (public authorities and private enterprises) takes place within different structures, with different tasks and competencies. PPP applies to any use of the resources of the business environment to meet social needs. At the same time, the resources attracted from the private sector can be different - both capital and know-how, as well as managerial experience.